2012
DOI: 10.1124/mol.112.078188
|View full text |Cite
|
Sign up to set email alerts
|

Crotamine Pharmacology Revisited: Novel Insights Based on the Inhibition of KV Channels

Abstract: Crotamine, a 5-kDa peptide, possesses a unique biological versatility. Not only has its cell-penetrating activity become of clinical interest but, moreover, its potential selective antitumor activity is of great pharmacological importance. In the past, several studies have attempted to elucidate the exact molecular target responsible for the crotamine-induced skeletal muscle spasm. The aim of this study was to investigate whether crotamine affects voltagegated potassium (K V ) channels in an effort to explain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 36 publications
4
47
0
3
Order By: Relevance
“…Crotamine inhibited the hKv1.3 channel (but not the hKv1.5 channel), which is consistent with a previous study that reported that crotamine selectively inhibits hKv1.1, hKv1.2, and hKv1.3 channels, but not hKv1.4 or hKv1.5 channels (Peigneur et al, 2012). This functionality suggests that the purified recombinant protein is correctly folded.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Crotamine inhibited the hKv1.3 channel (but not the hKv1.5 channel), which is consistent with a previous study that reported that crotamine selectively inhibits hKv1.1, hKv1.2, and hKv1.3 channels, but not hKv1.4 or hKv1.5 channels (Peigneur et al, 2012). This functionality suggests that the purified recombinant protein is correctly folded.…”
Section: Discussionsupporting
confidence: 89%
“…This functionality suggests that the purified recombinant protein is correctly folded. Crotamine purified from crude venom exhibits an IC 50 value for hKv channel inhibition of approximately 300 nM (Peigneur et al, 2012). The crotamine purified here from E. coli inhibited hKv1.3 characterized by an IC 50 value of 67 nM, which is approximately 4 times more active in comparison with crotamine purified from snake venom.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…One example of a multifunctional and versatile snake venom peptide that is structured by the central g-core and the canonical b-defensin fold is crotamine (Kerkis et al 2010; Rádis-Baptista and Kerkis 2011). Initially characterized from the venom of South American rattlesnake Crotalus durissus terrificus and described as a myotoxin with the ability to interfere with Na + -channel function, crotamine was demonstrated to possess multiple molecular functionalities, such as selective in vitro and in vivo anticancer cytotoxicity (Hayashi et al 2008;Pereira et al 2011;Kerkis et al 2014), biocide activity against bacteria and fungi (Oguiura et al 2011;Yamane et al 2013), selective interaction with the eukaryotic voltage K + channel (Yount et al 2009;Peigneur et al 2012), translocation across lipid bilayers and penetration into eukaryotic cells (Kerkis et al 2004), and interaction with nucleic acids and delivery of genes and probes (Nascimento et al 2007;Chen et al 2012). These properties equip crotamine with a unique versatility to be explored for the development of diagnostic probes and therapeutic peptides.…”
Section: Reptilian Antimicrobial Peptidesmentioning
confidence: 99%